SPE International Symposium on Oilfield Chemistry 2011
DOI: 10.2118/141179-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study On Admixtures For Calcium Aluminate Phosphate Cement Useful To Seal CCS Wells

Abstract: Conventional Portland cement is known to degrade under the attack of CO 2 . The failure is caused by formation of CaCO 3 which in the presence of wet CO 2 can leach as calcium bicarbonate Ca(HCO 3 ) 2 . This way, channels for further ingress and migration of carbon dioxide are created. Recently, a new binder system based on calcium aluminate phosphate cement has been developed which exhibits outstanding CO 2 resistance and temperature stability up to 320 °C. Main limitation of this novel binder system is a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On the basis of these mechanisms, non-Portland cement, and composite cement have been gradually developed. Calcium-aluminate cement, , sulfate-aluminate cement, and calcium phosphate-aluminate cement are all non-Portland cements and could be alternatives when being applied in the CO 2 storage process. Compared to conventional Portland cement, these three types of materials have less content of CaO, and many other components such as Al 2 O 3 and P 2 O 5 were added to prevent them from easily reacting with CO 2 like conventional Portland cement .…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…On the basis of these mechanisms, non-Portland cement, and composite cement have been gradually developed. Calcium-aluminate cement, , sulfate-aluminate cement, and calcium phosphate-aluminate cement are all non-Portland cements and could be alternatives when being applied in the CO 2 storage process. Compared to conventional Portland cement, these three types of materials have less content of CaO, and many other components such as Al 2 O 3 and P 2 O 5 were added to prevent them from easily reacting with CO 2 like conventional Portland cement .…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…These characteristics make it attractive in the construction of future wells for CCS. Dugonjic-Bilic et al (2011) tested the performance of a sealant composition based on CAC with a retarder in a CO 2 environment. They found that the ability of their composition to control water loss is suitable in CCS applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many polymeric additives are combined in cement slurry designs to control the properties of the cement slurry and ensure an even placement against the rock formation (Nelson and Guillot 2006, Bilic et al 2011, Cadix and James 2021. Fluid loss and rheology control additives are critical from this perspective to maintain the homogeneity of the slurry, prevent settling and retain water within the slurry as it is being pumped under high differential pressure against a porous rock formation.…”
Section: Introductionmentioning
confidence: 99%